2016
DOI: 10.1007/s10964-016-0471-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Interactive School-Based Program for Preventing Adolescent Sexual Harassment: A Cluster-Randomized Controlled Evaluation Study

Abstract: Many adolescents experience sexual harassment and victims of sexual harassment have higher risks regarding well-being and health behaviors such as higher risks of suicidal thoughts, suicidal ideation and feeling unsafe at school. A peer-performed play and school lessons on preventing sexual harassment behavior were presented to secondary school students. We evaluated its effectiveness, using a cluster-randomized controlled design to assign schools to an experimental condition [n = 14 schools; 431 students (51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 34 publications
2
80
0
8
Order By: Relevance
“…At the same time interventions designed particularly to deal with sexual harassment have proven ineffective with regard to affecting behavior (Connolly et al 2015;de Lijster et al 2016;Pina et al 2009). In developing interventions, we believe one must target the more common forms of peer sexual harassment, based upon future empirical knowledge on the active mechanisms driving this behavior.…”
Section: Future Researchmentioning
confidence: 99%
“…At the same time interventions designed particularly to deal with sexual harassment have proven ineffective with regard to affecting behavior (Connolly et al 2015;de Lijster et al 2016;Pina et al 2009). In developing interventions, we believe one must target the more common forms of peer sexual harassment, based upon future empirical knowledge on the active mechanisms driving this behavior.…”
Section: Future Researchmentioning
confidence: 99%
“…Obstaja namreč težnja, da se spolno nadlegovanje razume kot »izreden« pojav in ne kot vsakodnevni izraz razmerij moči med spoloma, ki se lahko manifestira v različnih situacijah in na več načinov. Najširše je spolno nadlegovanje v kontekstu šole definirano kot »nezaželena spolna pozornost, ki jo izkusijo številni adolescenti in ne vključuje samo fizičnih kontaktov, kot so denimo poljubljanje, objemanje in dotikanje, ampak tudi nefizične kontakte, kot so denimo spolne pripombe, šale, geste ali pogledi, kazanje eksplicitnih spolnih vsebin, sporočil ali zapisov ter razširjanje govoric s spolno vsebino« (de Lijster et al, 2016). Vendar so spolno nadlegovanje lahko tudi ravnanja, ki niso nujno videna kot neposredno »seksualna« (prim.…”
Section: Spolno Nadlegovanjeunclassified
“…The six studies above showed that sexual and reproductive education programs, in general, have positive impact to change teenagers sexual behavior (Adeleye et al, 2014;de Lijster, Felten, Kok, & Kocken, 2016;Denison et al, 2012;Mahat, Scoloveno, & Scoloveno, 2016;Menna, Ali, & Worku, 2015;Odundo, Anjuri, & Odhiambo) and other studies showed no significance between the health education school with sexual behavior (Jennings, Howard, & Perotte, 2014). However one study that shows two sexual behavior indicates that there is a significant one partner's behavior and sexual intercourse to abstain for a year in post © 2017 The author and GRDS Publishing.…”
Section: The Characteristics Studymentioning
confidence: 99%